Comparison of two techniques in proximal anastomosis in acute type A aortic dissection - Fang, Changcun; Gao, Shan; Ren, Xiao; Pang, Xinyan; Zhao, Xin; Ma, Zengshan; Wang, Chen; Liu, Kai (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: The proximal anastomosis is an important procedure during the acute type A aortic dissection (AAAD) surgery. The conventional method is double patch sandwich technique with Teflon felt. Adventitial eversion and prosthesis eversion technique as a novel approach has been applied on many patients in our center. Herein, we would introduce this technique, and evaluate the perioperative and one-year follow-up results of the different anastomosis methods. Methods: Between December 2017 and May 2021, 143 AAAD patients who underwent total arch replacement and frozen elephant trunk implantation were included in this retrospective study. Patients were divided into the eversion technique group (adventitial eversion and prosthesis eversion technique for proximal anastomosis, n=64) and the sandwich technique group (n=79). Results: The medical records were analyzed and compared between the groups. The mean operation time was 466±73 minutes in the eversion technique group and 513±81 minutes in the sandwich technique group (P<0.001). Compared with the sandwich technique group, the eversion technique group also showed a shorter time on proximal anastomosis (38±12 minutes vs. 58±20 minutes, P<0.001), cardiopulmonary bypass (195±26 vs. 211±40 minutes, P=0.003), and aortic cross-clamp (120±23 minutes vs. 134±27 minutes, P=0.002). Furthermore, a decreased proportion of ＞600ml fresh frozen plasmas transfusion was observed in eversion technique group (10.9% vs. 34.2%, P=0.002). No statistical differences were found in the postoperative morbidities and one-year follow-up outcomes. Conclusions: Proximal anastomosis using adventitial eversion and prosthesis eversion technique is a promising surgical option for AAAD patients, with favorable perioperative and one-year follow-up results.